SPDT discrete switch design using switchable SIW resonators for millimeter wave MIMO transceiver - Amirul Aizat Zolkefli; Badrul Hisham Ahmad; Noor Azwan Shairi; Adib Othman; Zahriladha Zakaria; Imran Mohd Ibrahim; Huda A. Majid (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
A single pole double throw (SPDT) discrete switch design using switchable substrate integrated waveguide (SIW) resonators is proposed in this paper. It was designed for the millimeter wave multiple input multiple output (MIMO) transceiver. An example application is for 5G communication in 26 GHz band. High isolation between transmitter and receiver (in the transceiver) is needed in SPDT switch design to minimize any high radio frequency (RF) power leakage in the receiver. Therefore, the use of switchable SIW resonators can achieve higher isolation if compared to the conventional series SPDT switch, where the isolation of the proposed SPDT is depend on the bandstop response of the SIW resonators. The switchable SIW resonators can be switched between allpass and bandstop responses to allow the operation between transmit and receive modes. As a result, the simulation and measurement showed that the proposed SPDT switch produced an isolation higher than 25 dB from 24.25 to 27.5 GHz compared to the conventional design.